1996
DOI: 10.1289/ehp.961041340
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of fluorosis and brick tea drinking in Chinese Tibetans.

Abstract: Brick tea-drinking fluorosis is an unusual environmental problem. As a result of an investigation of tea-drinking habits, total fluoride intakes, dental fluorosis, and skeletal fluorosis, this disease has been found in the Sichuan Province of China in Tibetans with a long history of drinking brick tea. The dental fluorosis investigation of 375 Tibetan children (213 males, 162 females) and 161 Han children (86 males, 75 females), 8-15 years of age, was carried out in Daofu County, Sichuan Province. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 3 publications
2
29
0
Order By: Relevance
“…Intervention trails are currently underway in some brick-teatype fluorosis endemic areas. The daily F intake of Tibetan children in school decreased from 6.23 mg/day/person to 1.65 mg/day/person after consuming the low-fluoride brick tea Table 2 Relation between F daily intake and the prevalence of dental fluorosis in children [4,31] Subject (ethnic group and area)…”
Section: Control and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention trails are currently underway in some brick-teatype fluorosis endemic areas. The daily F intake of Tibetan children in school decreased from 6.23 mg/day/person to 1.65 mg/day/person after consuming the low-fluoride brick tea Table 2 Relation between F daily intake and the prevalence of dental fluorosis in children [4,31] Subject (ethnic group and area)…”
Section: Control and Preventionmentioning
confidence: 99%
“…Large epidemiology observations showed that fluorosis could be caused by long-term consumption a large quantities of brick tea by some inhabitants of Tibet, Mongolia and some minorities in the west of China [4]. Bileissi et al found that the dental fluorosis in children was positively associated with the daily mean of tea drinking in a chronic dental fluorsis area in Jordan [5].…”
Section: Introductionmentioning
confidence: 99%
“…Even though some epidemiological reports were contradictory (Forster et al, 1995;Rondeau et al, 2000), there was a mounting scientific evidence suggesting a relationship between the neurotoxicity of Al and the pathogenesis of Alzheimer's disease (Aremu and Meshitsuka, 2006). Unbalance of F in the human body can cause dental caries and fluorosis (Cao et al, 1996;Browne et al, 2005;Cunha-Cruz and Nadanovsky, 2005). Therefore, it will be of theoretical and practical significance to study the Al and F contents in tea plants and factors influencing the uptake of Al and F from soils into tea plants for adjusting the condition of soil in tea garden and decreasing contents of Al and F in tea plants.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found fluorosis to be invariably associated with high concentrations of fluoride in drinking water [8,9]. High oral intake of fluoride results in physiological disorders, skeletal and dental fluorosis, thyroxine changes and kidney damage [10,11]. Fluorides accumulate in bones and teeth as fluorapatite and causes bone to become brittle [12,13].…”
Section: Introductionmentioning
confidence: 99%